Diversity of proteobacterial endosymbionts in hemlock woolly adelgid (Adelges tsugae) (Hemiptera: Adelgidae) from its native and introduced range. (4th March 2013) - von, Carol D.; Spaulding, Usha; Shields, Kathleen; Havill, Nathan P.; Rosa, Cristina; Hoover, Kelli
Summary Knowledge of intraspecific variation in symbioses may aid in understanding the ecology of widespread insects in different parts of their range. We investigated bacterial symbionts of Adelges tsugae, a pest of hemlocks in eastern North America introduced from Asia. Amplification, cloning, and sequencing of bacterial 16S rDNA, in situ hybridizations, and electron microscopy revealed that A. tsugae harbours up to five bacterial phylotypes, according to population. Three Gammaproteobacteria species are maternally transmitted. The first, designated 'Ca. Pseudomonas adelgestsugas' resides in the haemocoel, and was detected in all populations except Taiwan. The second phylotype, 'Ca. Serratia symbiotica', resides in bacteriocytes of populations on Tsuga sieboldii in Japan and in E. North America. The third phylotype, designated 'Ca. Annandia adelgestsuga', clustered within a lineage of several insect endosymbionts that included Buchnera aphidicola. It was detected in bacteriocytes in all populations, and in salivary glands of first instars. Two Betaproteobacteria phylotypes were detected in some Japanese T. sieboldii and eastern North America populations, and were observed only in salivary glands with no evidence of maternal transmission. Our results support the ideas that symbiont gain and loss has been volatile in adelgids, and that symbionts may help to trace the source of invasive species.